Caught on the Fringes of Life: Mothers' Lived Experiences of Initial Breastfeeding Complications. (July 2021) - Rydström, Lise-Lott; Tavallali, Azar; Sundborg, Eva; Berlin, Anita; Ranheim, Albertine
Becoming a parent changes one's life, and existential questions arise. Time and being oscillate between joy and powerlessness, vulnerability, and self-confidence, between harmony and unpreparedness. Breastfeeding, one of the first skills new mothers try to master, can be joyful and painful. The aim of this study was to develop a deeper understanding of the phenomenon of initial breastfeeding complications as they are lived and experienced by mothers and how these mothers can be supported. Twelve mothers were interviewed, and a phenomenological lifeworld approach was used. Nourishing an infant and having initial breastfeeding complications can be understood by the essence and its constituents. Expectations are fulfilled, and expectations come to naught when complications are experienced such as wavering between powerlessness and joy and finding solutions through resistance. The results suggest that lifeworld-led caring may lead to deepened acknowledgment and the possibility for mothers to feel supported in their extreme situations.